(untitled) (Salam International Academic Journal, 2025)
The discussion on the migration of scholars from the provinces of Herat, Balkh, Bust, and Baghlan is a scholarly and library-based research topic. The content of this study has been developed through the review and analysis of relevant books. This topic holds significant importance as it relates to a critical part of the country’s historical narrative, namely, the migration of scholars from specific regions of Afghanistan. The study begins with a brief introduction to the four mentioned provinces. It then proceeds to examine the migration of hadith scholars and jurists from these regions. For each province, a sample of notable hadith scholars and jurists is introduced, along with the names of the destinations to which they migrated. The reasons and factors underlying the migration of scholars are also analyzed in detail. Finally, the study explores both the positive and negative consequences of these migrations, presenting the outcomes separately. The article concludes with a summary of the main research findings.